Influence of Sociolinguistic Factors on Grammatical Competence of Lithuanian Used by Students Enrolled in Russian Gymnasiums - Bružaitė-Liseckienė, Justina (Pedagogika, 2020)
This article investigates the influence of sociolinguistic factors on the Lithuanian language grammatical competence of 11th grade (3rd gymnasium grade) students enrolled in Russian gymnasiums. The data of the study were collected in four high schools in Vilnius, where the language of instruction is Russian. 179 students participated in the study. To measure the grammatical competence of object marking in the Lithuanian language the Elicited Oral Imitation Test (Erlam 2006) and the task of narrative writing were used. A sociolinguistic questionnaire focused on the age of onset of Lithuanian and the linguistic behavior of students. The data were analyzed with R (R Core Team, 2013). Linear mixed effects models (LMM) were used to explore the relationship between sociolinguistic factors and students’ grammatical competence of the Lithuanian language. The results of LMM revealed that the students’ age of onset of Lithuanian affected their correctness in marking grammatical objects in Lithuanian. Students, who learned Lithuanian before the age of 4 performed better in the tasks than students who learned the language at the age of 6 or later. A strong positive correlation between the semestral grade of the Lithuanian language and literature at schools and students’ grammatical competence was also noticed. However, almost no factors of students’ linguistic behavior were significant in the analysis.